Validitas Media Pembelajaran Ispring Suite Berbasis Android Pada Pemahaman Shalat Jama’ dan Qashar - Rofidatul ‘Aisyah; Siti Sulaikho (Universitas Muhammadiyah Jember, 2021)
learning media iSpring Suite is an interactive learning media that combines audio, video and quiz maker. This learning media is the development of Microsoft PowerPoint which is already known by teachers and students. The purpose of this learning media is to facilitate understanding of Islamic Religious Education subjects, especially the material for praying jama' and qashar. The research subjects were seventh grade students of SMPN 2 Megaluh Jombang. The type of research is RnD with Borg and Gall model. 4D in question is the define (defining), design (design), develop (development), and disseminate (dissemination). Data collection techniques in the form of observation, interviews, and questionnaires. Observations were made on the learning process that took place in the classroom. Interviews were conducted with teachers to find out students' problems in understanding Islamic Religious Education lessons. Questionnaires to assess learning media were assessed by three experts, namely material experts, media experts, and linguists. The rating scale uses a Likert scale with 5 categories, namely very feasible, decent, fairly decent, less feasible, and very less feasible. The results of the assessment from material expert validators are 90.625% in the very appropriate category, the assessment from linguists is 90.63% in the very appropriate category, and the assessment from media experts is 80.88% in the appropriate category. The average value of the three experts is 87.26% with a very decent category. Thus, thelearning media is iSpring Suite Android-basedvery feasible to use.